Frost: a momentum-conserving CUDA implementation of a hierarchical fourth-order forward symplectic integrator. Issue 4 (11th January 2021) - Rantala, Antti; Naab, Thorsten; Springel, Volker
ABSTRACT: We present a novel hierarchical formulation of the fourth-order forward symplectic integrator and its numerical implementation in the GPU-accelerated direct-summation N -body code frost . The new integrator is especially suitable for simulations with a large dynamical range due to its hierarchical nature. The strictly positive integrator sub-steps in a fourth-order symplectic integrator are made possible by computing an additional gradient term in addition to the Newtonian accelerations. All force calculations and kick operations are synchronous so the integration algorithm is manifestly momentum-conserving. We also employ a time-step symmetrization procedure to approximately restore the time-reversibility with adaptive individual time-steps. We demonstrate in a series of binary, few-body and million-body simulations that frost conserves energy to a level of |Δ E / E | ∼ 10 −10 while errors in linear and angular momentum are practically negligible. For typical star cluster simulations, we find that frost scales well up to N_GPU^max4× N/10^5 GPUs, making direct-summation N -body simulations beyond N = 10 6 particles possible on systems with several hundred and more GPUs. Due to the nature of hierarchical integration, the inclusion of a Kepler solver or a regularized integrator with post-Newtonian corrections for close encounters and binaries in the code is straightforward.